2020
DOI: 10.1016/j.biopha.2020.110643
|View full text |Cite
|
Sign up to set email alerts
|

Drug repurposing of anti-infective clinical drugs: Discovery of two potential anti-cytokine storm agents

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Subsequent western blot experiments found that Trichomicin inhibited the Stat3 and NF-κB pathways and reduced the phosphorylation of Stat3 and p65 following LPS stimulation ( Figure 7 ). Through comparison, the anti-cytokine storm activity of Trichomicin was significantly stronger than that of entecavir ( Su et al, 2020 ). Trichomicin also showed good oral absorption and rapid uptake ( Zhu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent western blot experiments found that Trichomicin inhibited the Stat3 and NF-κB pathways and reduced the phosphorylation of Stat3 and p65 following LPS stimulation ( Figure 7 ). Through comparison, the anti-cytokine storm activity of Trichomicin was significantly stronger than that of entecavir ( Su et al, 2020 ). Trichomicin also showed good oral absorption and rapid uptake ( Zhu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages play a vital role in both SARS-CoV-2 virus -induced lung lesions and the host cytokine-mediated response ( 8 ). In our previous study, entecavir, a hepatitis B virus (HBV) inhibitor, was demonstrated to directly inhibit the release of cytokines in lipopolysaccharide (LPS) -stimulated macrophage model ( 27 ), which is a classic in vitro model to evaluate the anti-inflammatory activity of the drugs ( 28 ). Herein, we also examined whether these three neuraminidase inhibitors could inhibit the expression of inflammatory cytokines in LPS-stimulated macrophages in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…It is activated by post-translational modificiation as phosphorylation, and the IκB protein’s proteolytic degradation via enhanced IκB kinase (IKK) and NF-κB inducing kinase (NIK) ( 6 ). Activated NF-κB translocate to the nucleus and acts as a transcription factor that binds to the promoter region of inflammatory related genes, triggering their transcription ( 7 ). Hyperactivation of NF-κB increases inflammatory diseases and anti-inflammatory drugs inhibit the expression of inflammatory cytokine by attenuating the NF-κB pathway ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Activated NF-κB translocate to the nucleus and acts as a transcription factor that binds to the promoter region of inflammatory related genes, triggering their transcription ( 7 ). Hyperactivation of NF-κB increases inflammatory diseases and anti-inflammatory drugs inhibit the expression of inflammatory cytokine by attenuating the NF-κB pathway ( 7 ). Thus, NF-κB inhibitors have important clues for the drug development of inflammation responses and therapeutic paradigms to inhibit pathological inflammation.…”
Section: Introductionmentioning
confidence: 99%